2021
DOI: 10.1186/s12864-021-07994-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in gene expression of Tasmanian devil facial tumors despite minimal host transcriptomic response to infection

Abstract: Background Transmissible cancers lie at the intersection of oncology and infectious disease, two traditionally divergent fields for which gene expression studies are particularly useful for identifying the molecular basis of phenotypic variation. In oncology, transcriptomics studies, which characterize the expression of thousands of genes, have identified processes leading to heterogeneity in cancer phenotypes and individual prognoses. More generally, transcriptomics studies of infectious disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…We identified three species of novel RNA viruses in this study: two hepaciviruses (positive-sense RNA, family Flaviviridae), one in antechinus and one in a numbat, and a chu-like virus (negative-sense RNA virus, order Jingchuvirales) here named Tasmanian devil chu-like virus. The chu-like virus, which has an unsegmented, non-circular genome, was identified in a DFTD cell line that was cultured from primary tissue ( Kozakiewicz et al. 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified three species of novel RNA viruses in this study: two hepaciviruses (positive-sense RNA, family Flaviviridae), one in antechinus and one in a numbat, and a chu-like virus (negative-sense RNA virus, order Jingchuvirales) here named Tasmanian devil chu-like virus. The chu-like virus, which has an unsegmented, non-circular genome, was identified in a DFTD cell line that was cultured from primary tissue ( Kozakiewicz et al. 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As MtrBTN2 ploidy appears highly abnormal (varying between 8N to 18N, (18)), further investigations will be needed to determine whether the dysregulation of these DNA repair pathways favors recombination between homologous chromosomes and chromosomal abnormalities accumulation, or whether these pathways are activated in order to limit DNA damages. Interestingly, up-regulation of double-stranded DNA break repair via HR pathway was also found in DFTD (78).…”
Section: Resultsmentioning
confidence: 87%
“…Interestingly, up-regulation of double-stranded DNA break repair via HR pathway was also found in DFTD (78).…”
Section: Dna Repair Systems Are Dysregulatedmentioning
confidence: 83%
“…Expression of key adaptive immune genes decreased, and expression of some innate immune genes increased ( 21 ), whilst the T-cell repertoire constricted markedly ( 22 ). In contrast, a study using full transcriptomics showed little gene expression difference between infected and healthy animals ( 20 ). Our approach used both cross-sectional and longitudinal datasets, with a focus on DFTD infection, to allow insight into how individuals change their immune gene expression over the course of their life, particularly when confronted with DFTD infection.…”
Section: Discussionmentioning
confidence: 98%
“…Tasmanian devil responses to DFTD infection are complex, with no differences between the transcriptomes of healthy and DFTD infected animals detected in lip tissue ( 20 ). However, more targeted analysis from blood has shown shifts in immune gene expression with DFTD infection ( 21 ).…”
Section: Introductionmentioning
confidence: 99%